Fractionation of metabolite compound from Medinilla speciosa and their antioxidant activities using ABTS.+ radical cation assay - Vifta, Rissa Laila; Luhurningtyas, Fania Putri (Universitas PGRI Semarang, 2019)
Phenolic compounds are one of the main parts in secondary metabolites. Parijoto fruit is a family of Melastomataceae which contains flavonoids as phenolic compounds which are known to have antioxidant potential. Flavonoids have an-OH groups that play an active role as free radical scavengers. The study was conducted as initial screening in testing the antioxidant activity of extracts and fractions of the Parijoto fruit (Medinilla speciosa). The study began with the phytochemical screening process using the Thin Layer Chromatography method to ensure the presence of flavonoid content in extracts and fractions of parijoto fruit, then proceed with the measurement of antioxidant power. Testing the antioxidant activity using the ABTS method (2,2 azinobis (3-ethylbenzothiazolin) -6-sulfonic acid) which is specific, simple and easy to apply. Parijoto fruit extracts and fractions were made in a series of concentrations, measured antioxidant activity, and each IC50 value was determined. Phytochemical screening test results showed the presence of flavonoids in extracts and fractions of parijoto fruit. The results of measurements of antioxidant power in extracts and fractions of parijoto fruit gave IC50 values of 6,520 ppm in ethanol extracts with very strong antioxidant categories. The n-hexane fraction produced an IC50 value of 118,424 ppm with a moderate antioxidant category, while the IC50 value of ethyl acetate and ethanol fractions was 4,246 ppm and 3,874 ppm, respectively, with a very strong antioxidant category. The activity and value of IC50 produced by extracts and fractions of Parijoto fruits showed potential as a candidate of antioxidant.Keywords: ABTS, Antioxidant, Flavonoids, Medinilla speciosa, Phenolic